Seasonal quality of milk from Creole grazing goats, stabled Saanen and French-Alpine goats - Salgado-Beltrán, Víctor-Abrahán; Murillo-Amador , Bernardo; Nieto-Garibay, Alejandra; Montes-Sánchez, Juan-José; Aguilera, Narciso; Ortega-Pérez, Ricardo (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Goat milk production has been increasing in northern Mexico; however, there is little information available about its quality. Objective: To compare goat milk quality during three seasons among creole goats in a traditional grazing system and stabled Saanen and French-Alpine goats. Methods: An experiment was performed in a completely randomized nested design with seasonality factor (fixed effects) with three levels (rain, transition, and drought) and breed factor (fixed effect with three levels (Creole, Saanen and French-Alpine)) nested within the season-of-the-year factor. Fifteen goats were randomly selected: five Creole in the extensive grazing system, five stabled Saanen, and five stabled French-Alpine. The factors assessed in milk were fat content, non-fat solids, protein, lactose, salts, density, freezing point, conductivity, and pH (using a Lactoscan® device). Results: With respect to season for all the breeds: fat, non-fat solids, protein, lactose, and salt contents were higher (p≤0.05) for goats sampled in the rainy season, followed by drought and transition seasons, respectively. The variables related to milk quality by breed and season showed that milk fat content of creole goats was greater (p≤0.05) in the drought season; salt and non-fat content (p≤0.05) in the three seasons of the year; density and protein increased (p≤0.05) in the transition and rainy seasons, while lactose was greater (p≤0.05) in drought and rainy seasons; protein was greater (p≤0.05) in transition and rainy seasons; and the freezing point was lower (p≤0.05) in the transition season. Regarding conductivity, French-Alpine milk was greater (p≤0.05) in the drought season. Conclusion: Season of the year significantly affects milk quality, with increased quality during the rainy season in creole grazing goats.